Clinical impairments associated with ankle disability in patients with acute lateral ankle sprain - Young-Hyun Lee; Kang-Jun Lee; Seung-Hee Nam; Kyung-Min Kim (Frontiers in Public Health, 2025)
BackgroundAcute lateral ankle sprains (ALAS) are common musculoskeletal injuries among physically active individuals. While various impairments occur following ALAS, limited information is available on the factors contributing to ankle disability. This study aimed to investigate the association between the clinical impairments and ankle disability in patients with ALAS.MethodsWe conducted a cross-sectional design with 55 ALAS patients within two weeks of injury. Clinical impairments, including inflammatory symptoms (e.g., pain and swelling), restricted total ankle motion, joint laxity (e.g., anterior drawer test; ADT, inversion talar tilt test; ITT), and functional limitation were analyzed for their association with ankle disability assessed by the Foot and Ankle Ability Measure (FAAM) in Activities of Daily Living (ADL) and Sports (S) subscales.ResultsMultiple regression analysis revealed significant models that explained approximately 70% of the variance in FAAM subscales. The results indicated that swelling (β = −0.620 for FAAM-ADL, p < 0.01, β = −0.765 for FAAM-S, p < 0.01) and pain (β = −0.347 for FAAM-ADL, p < 0.01, β = −0.470 for FAAM-S, p < 0.01) were the most significant contributors to ankle disability in both subscales. Joint laxity measured by the ITT (β = −0.199, p < 0.05) negatively affected sports-related disability while restricted total ankle motion (β = 0.307, p < 0.05) had a positive effect. However, functional limitation was not significant in both subscales.ConclusionThese findings highlight the clinical impairments associated with ALAS, which contribute to ankle disability. Our results suggest that these impairments may be relevant considerations when designing early rehabilitation strategies (e.g., swelling reduction, pain control, and joint stability) for individuals with ALAS.